Методические советы и рекомендации педагогам-организаторам - Мануйлова С. Г. (Полиграф, 1999)
Экземпляры: УКП (20090720) / Инвентарный номер: АП19990320 / Сис.шифр: 74.200.5 / Авт.знак: М 54 / ГРНТИ: 14 / ББК: 74.200.585.82